Increasing JAK/STAT Signaling Function of Infant CD4+ T Cells during the First Year of Life - dela Peña-Ponce, Myra Grace; Rodriguez-Nieves, Jennifer; Bernhardt, Janice; Tuck, Ryan; Choudhary, Neelima; Mengual, Michael; Mollan, Katie R.; Hudgens, Michael G.; Peter-Wohl, Sigal; De Paris, Kristina (Frontiers in Pediatrics, 2017)
Most infant deaths occur in the first year of life. Yet, our knowledge of immune development during this period is scarce, and derived from cord blood only. To more effectively combat pediatric diseases, a deeper understanding of the kinetics and the factors that regulate the maturation of immune functions in early life is needed. Increased disease susceptibility of infants is generally attributed to T helper 2 (Th2)- biased immune responses. The differentiation of CD4+ T cells along a specific Th cell lineage is dependent on the pathogen type, and on costimulatory and cytokine signals provided by antigen-presenting cells. Cytokines also regulate many other aspects of the host immune response. Therefore, towards the goal of increasing our knowledge of early immune development, we defined the temporal development of the Janus kinase (JAK)/ Signal Transducers and Activators of Transcription (STAT) signaling function of CD4+ T cells using cross-sectional blood samples from healthy infants ages 0 (birth) to 14 months. We specifically focused on cytokines important in T cell differentiation (IFN- IL-12 and IL-4) or in T cell survival and expansion (IL-2 and IL-7) in infant CD4+ T cells. Independent of the cytokine tested, JAK/STAT signaling in infant compared to adult CD4+ T cells was impaired at birth, but increased during the first year, with the most pronounced changes occurring in the first 6 months. The relative change in JAK/STAT signaling of infant CD4+ T cells with age was distinct for each cytokine tested. Thus, while about 60% of cord blood CD4+ T cells could efficiently activate STAT6 in response to IL-4, less than 5% of cord blood CD4+ T cells were able to activate the JAK/STAT pathway in response to IFN-, IL-12 or IL-2. By 4-6 months of age, the activation of the cytokine-specific STAT molecules was comparable to adults in response to IL-4 and IFN-, while IL-2- and IL-12-induced STAT activation remained below adult levels even at 1 year. These results suggest that common developmental and cytokine-specific factors regulate the maturation of the JAK/STAT signaling function in CD4+ T cells during the first year of life.